The Evaluating the computational capacity of students in chess classes after applying tactical coordination exercises - Thanh Nguyen Duc; Minh Diu Ha (Journal of Physical Education (Maringá), 2025)
Through the research steps, 4 technical tests (Combined Attack; Checkmate in 2-4 Moves; Choosing the Optimal Solution; Strategy) and 2 psychological tests (Landont Open Loop; Taping Test) were identified as means to evaluate the effectiveness of applying tactical coordination exercises. At the same time, 17 objective and feasible groups of exercises were selected and applied for 4 months to contribute to improving the calculation ability of students in chess classes at Ho Chi Minh City University of Technology and Education (HCMUTE). The results showed that the growth rate after the experiment of the control group through individual tests was lowest at 0.47% (Tapping) and highest at 17.97% (Combined Attack), the average growth rate was 10.55%. Meanwhile, except for the Tapping test, the growth rate of the remaining 5 tests of the experiment group all increased significantly compared to the control group. Specifically, the growth rate of the individual tests of the experimental group was lowest at 2.31% (Tapping), and highest at 40.78% (Combination), the average growth rate reached 25.84%. This shows the correctness, rationality and effectiveness of the tactical coordination exercise groups selected to be included in the chess curriculum at HCMUTE.